Strong metal−support interactions in Cu(I)-dark TiO2 nanoscale photocatalysts prepared by pulsed laser ablation for hydrogen evolution reaction - Reutova, Olesya A.; Fakhrutdinova, Elena D.; Goncharova, Darya A.; Stadnichenko, Andrey I.; Stonkus, Olga A.; Kharlamova, Tamara S.; Svetlichnyi, Valerii A.; Vodyankina, Olga V. (ACS Applied Nano Materials)
In the present work, the highly effective nanoscale Cu-modified dark TiO2 photocatalysts for hydrogen evolution reactions are prepared by pulsed laser ablation with and without additional laser treatment (ALT). Transmission electron microscopy HR results show that copper is distributed along the dark titania surface both in the form of subnanometer oxide clusters and single atoms (SAs). After the ALT, the Cu dispersion increases, and a large number of SAs appear. The X-ray photoelectron spectroscopy data indicate that the increasing copper content as well as the ALT lead to an increase in the surface Ti3+ content. Copper on the surface exists in the Cu+ state, which is associated with the strong metal−support interaction (SMSI) effect between the defective TiO2 support and a SA/subnanometer cluster of copper. Photocatalytic activity of nanoscale Cu-modified dark TiO2 is studied in the hydrogen evolution from aqueous glycerol solution under irradiation with light-emitting diodes (LEDs) 375 (soft ultraviolet) and LED 410 (visible region). In all cases, the modification of the surface with copper significantly increases the hydrogen yield in both the UV and visible regions. The ALT also leads to an increase in the photocatalytic activity of materials due to an increase in the SMSI between copper species and the surface of the dark TiO2. For the process of photocatalytic hydrogen evolution, a mechanism is proposed, and the products of glycerol photooxidation are identified.